Antitumor Immune Response Triggered by Metal-Based Photosensitizers for Photodynamic Therapy: Where Are We? - Alain C. Jung (MDPI AG, 2021)
Metal complexes based on transition metals have rich photochemical and photophysical properties that are derived from a variety of excited state electronic configurations triggered by visible and near-infrared light. These properties can be exploited to produce powerful energy and electron transfer processes that can lead to oxygen-(in)dependent photobiological activity. These principles are the basis of photodynamic therapy (PDT), which is a clinically approved treatment that offers a promising, effective, and noninvasive complementary treatment or even an alternative to treat several types of cancers. PDT is based on a reaction involving a photosensitizer (PS), light, and oxygen, which ultimately generates cytotoxic reactive oxygen species (ROS). However, skin photosensitivity, due to the accumulation of PSs in skin cells, has hampered, among other elements, its clinical development and application. Therefore, these is an increasing interest in the use of (metal-based) PSs that are more specific to tumor cells. This may increase efficacy and corollary decrease side-effects. To this end, metal-containing nanoparticles with photosensitizing properties have recently been developed. In addition, several studies have reported that the use of immunogenic/immunomodulatory metal-based nanoparticles increases the antitumor efficacy of immune-checkpoint inhibitor-based immunotherapy mediated by anti-PD-(L)1 or CTLA-4 antibodies. In this review, we discuss the main metal complexes used as PDT PSs. Lastly, we review the preclinical studies associated with metal-based PDT PSs and immunotherapies. This therapeutic association could stimulate PDT.